An approach to the prospects of business English learning - VASILESCU, Ruxandra (Annals of Spiru Haret University. Economic Series, 2010)
The future of English as a global language has widely been discussed for over 10 years, starting with David Graddol (1997), a language researcher and lecturer at the Open University in Britain, in his famous work ‘The Future of English’, to so many other language researchers, so much inspired by Graddol’s book. Whether English will keep its supremacy as THE tool of communication in the future world is still debatable, fact is that English is still the language of business and information technology and it shall stay so for quite a while, in spite of the challenges coming from Spanish, French, German, Russian and… Mandarin. Once we acknowledge that, the question is: how can the teaching/learning process be improved in the future for a better and faster acquisition of English as the language of choice in the business world?